Cerebrovascular Infarction Presenting as Bilateral Internuclear Ophthalmoplegia in a 75 y/o Patient - J. Agustin, Kim (Journal of Ophthalmic Science, 2021)
Objective To present a case of Bilateral Internuclear Ophthalmoplegia in a 75yo patient Case Description A 75 year old, Filipino, male, known hypertensive for 10 years, but not compliant to medications, presented with a sudden onset binocular horizontal, diplopia and bilateral exotropia associated with dizziness. No other symptoms like slurring of speech, body weakness, numbness were noted. Primary gaze exotropia, abduction nystagmus, gaze evoked vertical nystagmus were also noted. Imaging was done which revealed hypodense focus in the subcortical region of the right centrum semiovale extending to the right corona radiata, with unremarkable orbits, midbrain and pons findings. WEBINO was still considered even without the presence of a pontine lesion in the imaging. The patient was advised patching and was asked to follow up after a month.
Keywords: Bilateral Internuclear Ophthalmoplegia; Cerebrovascular Infarction; Bilateral Exotropia; Diplopia; Nystagmus